الهوية وتشظي الذات في" رواية أقاليم الخوف" ل(فضيلة الفاروق) "دراسة ثقافية" Identity And Loss Self In ' The Novel Regions Of Fear ' (fadhila El Farouk) ' Cultural Study' - حميدة, قادوم (جامعة الوادي - University of Eloued, 2021)
ملخص: تناولت الرواية العربية المعاصرة بصفة عامة، والنِّسائية بصفة خاصة قضية الصراع والجدل القائم بين الشرق والغرب، وهو صراع ظهر نتيجة الصراع الديني والحقد الاستعماري الدَّفين ضدَّ العرب بصفة عامة، والمسلمين بصفة خاصة. وأدَّى ذلك إلى استفراد الغرب بالمركز في الوقت الذي أُزيح فيه الشرق إلى الهامش بوصفه متخلفا وجاهلا. وشكَّلت تلك المواقف المعادية للشرق ردود فعل حاسمة لدى المبدعين والمبدعات تجلَّت في نصوصهم الروائية التي حاولوا من خلالها إعادة الاعتبار للشرق العربي والتَّصدي لكل المؤامرات التي تسعى إلى طمس هوية الشرقي وعقيدته ولغته. تمثل رواية" أقاليم الخوف" واحدة من أبرز الروايات التي اهتمت بقضية الهوية والصراع القائم بين الشرق والغرب، عالجت من خلالها (فضيلة الفاروق) الصراع الديني وموقف الآخر الغربي من الأنا الشرقية، وهي المواقف التي طالما جعلت الغرب في مرتبة الصدارة، وجعلت الشرق مجرد تابع لها. وهذا ما نروم الخوض فيه من خلال هذه الدِّراسة التي تركز على جملة من العناصر وفق دراسة ثقافية نستجلي من خلالها فعل النَّسق المضمر والجمل الثقافية التي توظفها الروائية في هذا النَّص السردي، وتتمثل أساسا في: سؤال الهوية وقلق الانتماء، قرار الانفصال وحلم التغيير وصراع الأديان بين المعلن والمضمر، ونظرة الآخر المسيحي للشرق الإسلامي. Abstract: The contemporary Arab novel in general and feminism novel in particular, dealt with the question of conflict and controversy between east and west, which appeared as a result of religious conflict and hidden colonial hatred against Arabs in general and Muslims in particular. This led the west to distinguish the center, while the east was moved to the margin as backward and ignorant. These anti-oriental attitudes formed decisive reactions among the creators, reflected in their narrative texts, through which they tried to restore respect for the Arab east and confront all the conspiracies that seek to obscure the identity, the eastern belief and language. "Regions of Fear" is one of the most prominent novels that deal with the question of identity and the conflict between east and west, through which (Fadhila El Farouk) dealt with religious conflict and the position of the other westerner on the eastern ego, it’s the positions that have long made the west in the avant-garde and made the east just a follower. This is what we intend to deepen through this study, which focuses on a certain number of elements according to a cultural study, through which we express the tacit form and the cultural sentences that the novelist uses in this narrative text, it is mainly represented in: the question of identity and the anxiety of belonging, the decision to separate and the dream of change and the conflict of religions between the professed and the conscientious and the Christian vision to the Islamic East.
مقال
Keywords: صراع، حضاري، هوية، شرق ، غرب; Civilizational, Conflict, Identity, East, West.